Ряд Вольтерра для моделі Ходжкіна-Хакслі нейрона - Романишин, Ю.М.; Кохалевич, Ю.Р.; Пукіш, С.Р. (Моделювання та інформаційні технології, 2010)
The features of calculation of Volterra kernels for Hodgkin-Huxley neuron model are considered. The systems of four linear equations for spectra of three first Volterra kernels are obtained. Symbolic Math Toolbox of MATLAB system for obtaining first and second derivatives of Hodgkin-Huxley equations functions, for solving the systems of linear equations and for inverse Fourier transforms is used.